The Role of Entrepreneurial Cognition in the Internationalization of Small and Medium Enterprises: A Systematic Literature Review - Mentari, Sriyani; Sudarmiatin; Pratikto, Heri (International Journal Administration, Business & Organization, 2026)
This research utilizes a systematic literature review (SLR) to investigate the impact of entrepreneurial cognition on the international expansion of small and medium-sized enterprises (SMEs). While it is widely acknowledged that cognitive elements significantly affect how SMEs behave in foreign markets, current research remains scattered across diverse theoretical frameworks and constructs. This study analyzes 24 empirical papers from 2015 to 2025 sourced from Google Scholar and Scopus. The analysis reveals that entrepreneurial cognition is a multifaceted concept involving a global mindset, entrepreneurial orientation, managerial cognitive traits, and the ability to recognize opportunities. Furthermore, these cognitive processes are vital in driving internationalization by molding a firm's global perspective and helping leaders identify foreign market prospects. The findings also show that cognitive drivers impact international growth and export success, frequently through intermediate factors like learning orientation, innovation capacity, and decision-making frameworks. This research enhances the microfoundational perspective of SME expansion by focusing on the cognitive attributes of decision-makers rather than just structural factors.